The Role of Herbal Adaptogens and Immunomodulators in Dietary Food and Phytotherapy - Rybak, Oksana; Hudz, Nataliia; Svidenko, Lyudmila; Grygorieva, Olga; Makarenko, Oleksandr; Brindza, Jan (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
It was established that phytoadaptogens and immunomodulators are widely used in the composition of dietary food and pharmaceutical products. Phytoadaptogens positively affect the nervous system: normalize the processes of excitation and inhibition in the cerebral cortex, reduce fatigue in physical and mental stress, improve memory, etc. The general adaptogenic action is strengthened by antioxidant and immunomodulating properties of biologically active substances of plant material, bee bread and bee pollen. An analysis of the literature data shows that the immunostimulating and adaptogenic properties of above mentioned natural products are due to the presence phenylpropanoids and polysaccharides. Our attention was focused on a powerful antioxidant and vitamin product with anabolic effect – juice from fruits of Arónia mitschurínii Skvortsov et Maitulina, stimulating the central nervous system – fruits of Schisándra chinénsis (Turcz.) Baill, an immunostimulating agent – Echinácea purpúrea (L.) Moench, and also on bee bread and Lophanthus anisatus Benth. Fruits of chokeberry contain a large amount of B vitamins, phenolic acids and P-vitamin bioflavonoids. Lignan compounds of Schisandra chinensis were reported to possess strong antioxidant activity, which block processes of free radical oxidation and prevent the development of oxidative stress. The most characteristic component of Echinácea purpúrea is chicory acid, which determines the immunomodulation and antiviral activity. Bee pollen and bee bread are rich in polyphenols. We conduct research on the development of food and pharmaceutical products with an adaptogenic and immunostimulating effect on the basis of above mentioned natural products of sector of mobilization and saving of herbal resources of the rice institute of the National Agrarian Academy of Sciences of Ukraine, M.M. Gryshko National Botanical Garden of Ukraine and Institute of Biodiversity Conservation and Biosafety of Slovak University of Agriculture in Nitra.